IMPLEMENTASI NILAI DISIPLIN DAN TANGGUNG JAWAB DALAM EKSTRAKURIKULER PRAMUKA DI SEKOLAH DASAR - Rijal Sianturi; Yakobus Ndona; Daulat Saragi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the application of the values ​​of hard work and responsibility in extracurricular Scouting activities in elementary schools. Using a qualitative descriptive approach, data were obtained through observation, interviews, and documentation involving the principal, Scout leaders, and students. The results indicate that the values ​​of hard work and responsibility are instilled through practical activities, competitions, and outdoor activities that foster discipline and a sense of responsibility in students. This study recommends reinforcing these character values ​​in learning and suggests further study of other character values.